Prognostic Value of Coronary Artery Calcium Score in Hospitalized COVID-19 Patients - Luchian, Maria-Luiza; Lochy, Stijn; Motoc, Andreea; Belsack, Dries; Magne, Julien; Roosens, Bram; de Mey, Johan; Tanaka, Kaoru; Scheirlynck, Esther; Boeckstaens, Sven; Van den Bussche, Karen; De Potter, Tom; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The association of known cardiovascular risk factors with poor prognosis of coronavirus disease 2019 (COVID–19) has been recently emphasized. Coronary artery calcium (CAC) score is considered a risk modifier in primary prevention of cardiovascular disease. We hypothesized that the absence of CAC might have an additional predictive value for an improved cardiovascular outcome of hospitalized COVID–19 patients. Materials and methods: We prospectively included 310 consecutive hospitalized patients with COVID–19. Thirty patients with history of coronary artery disease were excluded. Chest computed tomography (CT) was performed in all patients. Demographics, medical history, clinical characteristics, laboratory findings, imaging data, in–hospital treatment and outcomes were retrospectively analyzed. A composite endpoint of major adverse cardiovascular events (MACE) was defined. Results: 280 patients (63.2 ± 16.7 years old, 57.5 % male) were included in the analysis. 46.7% patients had a CAC score zero. MACE – rate was 21.8% (61 patients). The absence of CAC was inversely associated with MACE (OR 0.209, 95% CI 0.052 – 0.833, p=0.027), with a negative predictive value of 84.5%. Conclusion: The absence of CAC had a high negative predictive value for MACE in patients hospitalized with COVID -19, even in the presence of cardiac risk factors. A semi-qualitative assessment of CAC is a simple, reproducible and non-invasive measure that may be useful to identify COVID-19 patients at a low risk for developing cardiovascular complications.